Stake's Countenance Evaluation Method on Occupational Health and Safety Implementation in Electronics Engineering Education's Student Industrial Internship - Munir, Muhammad; Jati, Mentari Putri; Wulandari, Bekti; Dewanto, Satriyo Agung (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2022)
This paper discusses the evaluation of the implementation of Occupational Health and Safety (OHS) in student industrial internships. Due to the possibility of the risk of work accidents on industrial internship students are prone to occur. Currently, there are still few who discuss the evaluation of OHS implementation as the basis for carrying out sustainable action efforts. Based on the evaluation carried out, the OHS Implementation in Electronics Engineering Education's Student Industrial Internship has been feasible and follows applicable laws and regulations. The results of this evaluation can provide ideas for increasing sustainable action efforts regarding OHS in Student Industrial Internships.